2014
DOI: 10.4067/s0717-97072014000200003
|View full text |Cite
|
Sign up to set email alerts
|

Development of an Active Film With Natural Zeolite as Ethylene Scavenger

Abstract: Ethylene (C 2 H 4 ) acts as a plant hormone, growth regulator that has a number of effects on the growth. Ethylene accelerates respiration, leading to maturity and also softening and ripening of many kinds of fruits. Although ethylene has some positive effects, it is often hazardous to the quality and shelf-life of fruits and vegetables. The removal of ethylene and/or inhibition of the effect of ethylene in stored environments is fundamental to maintaining postharvest quality of climacteric produce. In this st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 44 publications
(13 citation statements)
references
References 29 publications
(46 reference statements)
1
12
0
Order By: Relevance
“…Afterwards, all glass containers were stored at 25°C for 35 days. The amount of ethylene was determined every 7 days according to the method of Coloma et al with modification. Each container was vigorously shaken to increase the dispersion of gas.…”
Section: Methodsmentioning
confidence: 99%
“…Afterwards, all glass containers were stored at 25°C for 35 days. The amount of ethylene was determined every 7 days according to the method of Coloma et al with modification. Each container was vigorously shaken to increase the dispersion of gas.…”
Section: Methodsmentioning
confidence: 99%
“…This is because present technologies tend to have high transportation and operation costs, energy demands, and potentially produce toxic chemicals . Ethylene removal using zeolite as an adsorbent has received considerable attention in both industry and agriculture application . Trinh et al .…”
Section: Introductionmentioning
confidence: 99%
“…compared the efficiency of three different zeolites for adsorbing ethylene from an air steam and showed that silver (1.0%)/13X zeolite had high ethylene adsorption affinity. Even though zeolite has a strong ethylene adsorption affinity, its adsorption capacity is limited by its porosity and chemical nature . Improvement of ethylene removal can be achieved by doping catalysts or nanoparticles (NPs), such as palladium (Pd), titanium, copper, rhodium, and cobalt, onto zeolite or other carrier .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations